Surface‐Functionalized Carrier‐Free Drug Nanorods for Leukemia. Issue 2 (16th May 2018) - Krishnan, Vinu; Sarode, Apoorva; Bhatt, Rohit; Oliveira, Joshua D.; Brown, Tyler D.; Jiang, Y. P.; Reddy Junutula, Jagath; Mitragotri, Samir
Abstract: Pure drug nanoparticles have emerged as an alternate method for formulating extremely hydrophobic drugs. Herein, a simple and efficient process for synthesizing PEGylated and antibody‐conjugated, carrier‐free nanomedicine is reported as a promising strategy to deliver the drug, Camptothecin (CPT) for aggressive circulating tumors such as Acute Myeloid Leukemia (AML). Size, shape, and surface morphology of pure drug nanorods (NRs) are examined and characterized by a variety of techniques. Incorporation of polyethylene glycol (PEG) onto the particle changed its surface charge and topography while affecting its drug‐dissolution kinetics. Furthermore, the toxicity of PEGylated versus non‐PEGylated forms of humanized anti‐CD33 antibody (Hu195Ab)–coated CPT NRs are compared. Hu195Ab drug‐linked NRs increased cell killing in leukemic cells and surface PEGylation show reduced non‐specific uptake in cells. The results demonstrate that surface‐modified carrier‐free nanodrugs could have significant implications in cancer drug delivery for treating AML. This would be the first instance of studying the potential of surface‐functionalized carrier‐free drug NRs in the treatment of leukemia. Abstract : Herein, a simple, facile, and efficient process for synthesizing polyethylene glycol (PEG)‐ylated and antibody‐conjugated carrier‐free nanomedicine as a promising strategy to deliver extremely hydrophobic drugs such as camptothecin for aggressive circulating tumors like acute myeloid leukemia is reported. The results demonstrate that surface‐modified carrier‐free nanodrugs could have significant implications in cancer drug delivery for treating leukemia.